Model of Madrasah Al-Qur'an in Correctional Institution (Case Study of Class IIA Correctional Institution Yogyakarta) - Munjahid, Munjahid; Kuswanto, Heri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to determine the implementation, implications, supporting and inhibiting factors, and the Madrasah al-Qur'an Al Fajar model in Class IIA Correctional Institution Yogyakarta. This research is a field research using qualitative methods and phenomenological approaches. Data collection techniques are done through interviews, observations, and documentation, while data analysis uses Mautakas' phenomenological theory. The study results show that the implementation of Madrasah Al-Qur'an Al Fajar is driven by three agencies, namely the Class IIA Yogyakarta Prison, the Ministry of Religious Affairs of Yogyakarta, and BAZNAS DIY. Activities are implemented on Monday, Tuesday, Wednesday, Thursday, and Saturday with learning methods that include lectures, sorogan, bandongan, questions and answers, demonstrations, practices, examples, and habituation. The model of Madrasah Al-Qur'an Al Fajar is a madrasah that is managed in a modern and synergistic manner so that it can change the religious behavior of students for the better than before. The implementation of this Madrasah Al-Qur'an implies that students become diligent in reading the Qur'an, be tawadu', be polite and friendly, respect each other, be orderly in worship, be able to become khatib, imam, teaching assistant, and make speeches, with increased awareness and peace of mind. Factors supporting the success of this Madrasah include funds, Ustaz, management,